Overview of performance compatibility issues of GCLs with respect to leachates of extreme chemistry. Issue 2 (April 2014) - Bouazza, A.; Gates, W.P.
Abstract : ABSTRACT: Geosynthetic clay liners (GCLs) are frequently used in lieu of, or as an augmentation to, compacted clay liners as secondary hydraulic barriers in municipal solid waste containment facilities. GCLs are lately being assessed for use in industrial and mining applications, not only for the temporary storage of process waters and permanent disposal of tailings, but also beneath heap leach pads, where their performance will be subjected to loads, hydraulic heads and leachate chemistries outside the normal conditions found in conventional municipal solid waste landfills for which they were designed. This paper considers recent limited research assessing the compatibility of GCLs to leachates having extreme chemistry. Extreme chemistry is here defined as strongly alkaline (pH > 12), strongly acidic (pH < 3) and hypersaline (> 1 M). Based on the limited research available, GCLs cannot be expected to perform for the long-term when in contact with strongly acidic leachates; however there exists some indication for the possibility of inducing conditions for pore clogging that may assist their performance in the short term. Many GCLs probably can exhibit long-term performance objectives for strongly alkaline leachates. In both extreme pH ranges, leachate ionic strength and the potential for cation exchange have the greatest negative effects on bentonite swelling and GCL hydraulic conductivity. Future developments toward improving bentonite resistance to leachates having extreme chemistry should focus on experiments that underpin the potential mid- to long-term performance of GCLs and undertake to evaluate, as far as possible, changes in leachate chemistry and bentonite mineralogy involved in loss of field performance.